What Makes an Excellent Teacher? Insights From Junior High School Students With a History of Disruptive Behavior - Graham, Linda J.; Tancredi, Haley; Gillett-Swan, Jenna (Frontiers in Education, 2022)
Evidence of the powerful relationship between what teachers do and how effectively their students learn has led to reforms aimed at improving the quality of teaching. These have manifested in different ways and at different times internationally with most jurisdictions now paying increased attention both to the initial and ongoing education of teachers, as well as methods to assess, reward and improve performance in the classroom. Predominant among these approaches are frameworks that define observable elements of teaching for which there is evidence showing benefit for student learning, engagement and behavior. We contend that even the best of these do not go far enough, as they do not explicitly consider students with disability, even those in everyday classrooms whose behavior suggests their needs are not being met. In this paper, we report findings from in-depth interviews with 50 Grade 7 to 10 students with a history of disruptive and disengaged behavior. Students were first asked for their views on “what makes an excellent teacher” and then to describe what those teachers do to help them learn. Analysis yielded interesting results with these students emphasizing aspects of teaching that represent an essential—but from our observation—often absent “top layer” that is necessary for quality teaching to become inclusive teaching.